Spontaneous Haemophilia in a Female - Braun, E. H; Stollar, David B. (Thrombosis and Haemostasis, 1960)
A case of haemophilia in a young white girl is described. There was a history of bleeding from birth. The thromboplastin generation test was grossly abnormal and A. H. G. levels were below 1%. Bleeding time and capillary morphology was within normal limits. Dental extraction after transfusion caused almost uncontrollable haemorrhage.A complete family history was obtained for four generations. There was no case of a “bleeder” amongst these.The girl’s apparent sex was confirmed by sex chromatin studies.